2020
DOI: 10.3390/s20051353
|View full text |Cite
|
Sign up to set email alerts
|

The Algorithm and Structure for Digital Normalized Cross-Correlation by Using First-Order Moment

Abstract: Normalized cross-correlation is an important mathematical tool in digital signal processing. This paper presents a new algorithm and its systolic structure for digital normalized cross-correlation, based on the statistical characteristic of inner-product. We first introduce a relationship between the inner-product in cross-correlation and a first-order moment. Then digital normalized cross-correlation is transformed into a new calculation formula that mainly includes a first-order moment. Finally, by using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…We calculated the cross-correlation function using the Fast Fourier Transform mode of Scipy numerical library (v. 1.10) 55 . The computational complexity of this algorithm is 56 . The time of particular cross-correlation computation is 1199.46 ms.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the cross-correlation function using the Fast Fourier Transform mode of Scipy numerical library (v. 1.10) 55 . The computational complexity of this algorithm is 56 . The time of particular cross-correlation computation is 1199.46 ms.…”
Section: Methodsmentioning
confidence: 99%
“…In order to describe the detailed normalized correlation concept, we need to know the cross-correlation definition. Cross-correlation is the term that describes an inner product over two sensor data sequences [ 32 ]. where f(n) is the function per-unit conversion current value of the LCC line and g(n) is the function per-unit conversion current value of the VSC line.…”
Section: Cyber Physical System Threat Modelingmentioning
confidence: 99%
“…Systolic arrays have been proved to allow efficient VLSI implementations, as shown in [15][16][17][18][19]. It has been demonstrated that they best satisfy the trade-off between area and execution time for some important discrete transforms, as shown in [20].…”
Section: Introductionmentioning
confidence: 99%